Can capital requirements induce private monitoring that is socially optimal? - Kopecky, Kenneth J.; VanHoose, David (Journal of Financial Stability, 2012)
This paper develops a framework for analyzing socially and privately optimal bank loan-monitoring decisions, with and without capital regulation. In contrast to the monitoring decision of a social planner who seeks to maximize the utility of aggregate consumption, banks choose to monitor only if doing so is consistent with maximizing the market value of equity. As a consequence, socially and privately optimal monitoring choices can diverge. Under some circumstances, appropriately configured capital regulation can bring private loan-monitoring decisions into line with those of the social planner. Nevertheless, the capital ratio required to attain this outcome hinges on a number of factors that are likely to be economy-specific, including the banking system's monitoring technology and its exposure to default. Thus, it is unlikely that a unique capital ratio will be able to induce socially optimal monitoring in all economies.